Phylogenetic relationships of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species - Roggero, Angela; Stanbrook, Roisin; Josso, Jean-François; Barbero, Enrico; Palestrini, Claudia (Zootaxa, 2017)
Two new Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini) species were recently found among samples from Malawi and Kenya, and are here described as Epidrepanus nyika new species and Epidrepanus kenyensis new species. Previously, the Afrotropical genus Epidrepanus Roggero, Barbero & Palestrini, 2015 was known only for three species: Epidrepanus caelatus (Gerstaecker, 1871), E. pulvinarius (Balthasar, 1963), and E. schimperi (Janssens, 1953). Morphological features (head, pronotum, elytra, epipharynx, and hindwing) were analysed using geometric morphometrics, whose results confirmed that the two new species are closely related to the known Epidrepanus species. A combined phylogenetic approach with TNT software was used to evaluate the phylogenetic relationships within Drepanocerina, corroborating the taxonomic position of Epidrepanus as a well-differentiated taxon. The phylogenetic results were integrated with the distribution data, and then processed with dispersal-vicariance analysis using RASP (Reconstruct Ancestral State in Phylogenies), while the speciation mechanisms were highlighted using VIP (Vicariance Inference Program). Both biogeographical analyses confirmed that the central East Africa area was the ancestral area of Epidrepanus. The genus was then interested by two basal vicariant and subsequent multiple dispersal events, leading to the present-day distribution.